2009
DOI: 10.1292/jvms.001579
|View full text |Cite
|
Sign up to set email alerts
|

A High Percentage of Pigs Born Dead in Litters in High-, Intermediate- and Low-Performing Herds

Abstract: ABSTRACT. The objectives of the present study were to measure a percentage of pigs born dead in the number of total pigs born (PPBD), and to investigate an association between PPBD and total pigs born by parity groups and three herd groups formed on the basis of the pigs weaned per mated female per 6 years (PWMFY). The studied data included 236,805 parity records of 51,443 sows in 110 herds. The three herd groups, high-, intermediate-and low-performing herds, were formed on the basis of the upper and lower 25t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Additionally, the number of pigs born dead does not account for the association between the total pigs born and the pigs born dead, although the number of pigs born dead increases as the number of total pigs born increases 6,23) . The percentage of pigs born dead in the total pigs born is another measurement that includes the information on the total pigs born and pigs born dead in performance and health of the herd 15) .…”
Section: Number Of Pigs Born Dead or A Percentage Of Pig Born Deadmentioning
confidence: 99%
“…Additionally, the number of pigs born dead does not account for the association between the total pigs born and the pigs born dead, although the number of pigs born dead increases as the number of total pigs born increases 6,23) . The percentage of pigs born dead in the total pigs born is another measurement that includes the information on the total pigs born and pigs born dead in performance and health of the herd 15) .…”
Section: Number Of Pigs Born Dead or A Percentage Of Pig Born Deadmentioning
confidence: 99%
“…The effect of herd size on piglet preweaning mortality maybe related with postpartum management and quality of stock persons. Hoshino et al ( 2009) demonstrated that high-performing herd in Japan had a lower number of pig born dead than low-performing herd.…”
Section: List Of Tablesmentioning
confidence: 97%
“…On the other hand, high ambient temperature may decrease feed intake of the lactating sows due to heat stress This may affect milk production and decrease the piglet body weight gain ( McNamara and Pettigrew, 2002) . On average, preweaning mortality in large herds was lower than that in small herds ( Friendship et al , 1986;Hoshino et al , 2009;Nuntapaitoon and Tummaruk, 2013a) . The effect of herd size on piglet preweaning mortality maybe related with postpartum management and quality of stock persons.…”
Section: List Of Tablesmentioning
confidence: 99%
See 2 more Smart Citations